Feature Assessment of LMS by Senior High School Teachers and Student: A Basis for LMS Improvement - Christopher B. Capul; Shaira Marie J. Castillo; Katherine D. Tan; Ariel A. Briones; Marian G. Abad; Frederick Flores Patacsil (Universitas Negeri Makassar, 2022)
In this paper, three learning management systems (LMS), namely Google Classroom, Moodle, and Schoology, were evaluated and assessed based on how diverse school users regarded them. According to the findings of the study, teachers and their students were competent and satisfied enough to use the various LMSs during their asynchronous learning sessions. Teachers and students concur that their LMSs are very effective, user-friendly, simple to utilize, and provide accurate results. Teachers concurred that they can readily personalize their LMS by designing and assigning activities, assignments, and assessments, uploading learning resources, and setting suggested due dates. Finally, the opinions and suggestions of respondents regarding the improvement and integration of new features into various LMS were discussed. Despite various problems, the fundamental finding of this study is that using an LMS to organize, record, evaluate, and monitor students' performance makes duties easier for teachers and distant learners.